Innovation modes in SMEs: Mechanisms integrating STI-processes into DUI-mode learning and the role of regional innovation policy - Harm Alhusen; Tatjana Bennat (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2019)
Innovation processes consist of interactive learning mechanisms that combine different knowledge sources. Using a set of 72 exploratory interviews with small- and medium-sized enterprises (SMEs) and regional innovation consultants, this paper analyzes the combination of STI (science-technology -innovation) and DUI (innovation based on learning-by-doing, -using and -interacting) modes of innovation. We show that SMEs integrate STI-based knowledge into DUI-routines through mechanisms with varying levels of complexity. The mechanisms we describe differ with respect to a) effects on innovativeness, b) the absorptive capacities required and c) incurred costs. Based on these mechanisms, d) cognitive, organizational and financial barriers to combinatorial innovation modes are derived. We find that e) regional innovation consultancies play an important role in fostering combinatorial innovation modes. We therefore explore the role of regional innovation policy and its effects on firms' combination of innovation modes. Our findings point out innovation drivers that facilitate SMEs' capacity to absorb STI-based knowledge. Based on our empirical findings, we derive implications for innovation policy with regards to absorptive capacities in SMEs.
Keywords: D23; D83; L10; L22; O31; O33; O38; 330; Innovation modes; DUI; Regional Innovation System; R&D cooperation; Knowledge bases; Regional innovation policy